Environmental induced variations in leaf dark respiration and net photosynthesis of Quercus ilex L. - Gratani, L; Varone, L; Bonito, A (Photosynthetica, 2007)
The relationships between dark respiration rate (RD) and net photosynthetic rate (PN) in Quercus ilex L. shrubs growing at the Botanical Garden in Rome were analysed. Correlation analysis of the data sets collected in the year 2006 confirmed the dependence among the considered leaf traits, in particular, RD was significantly (p<0.05) correlated with PN (r = 0.40). RD and PN increased from March to May [1.40±0.10 and 10.1±1.8 μmol(CO2) m –2 s –1 mean values of the period, respectively], when air temperature was in the range 14.8–25.2 °C, underlining the highest metabolic activity in the period of the maximum vegetative activity that favoured biomass accumulation. On the contrary, the highest RD [1.60±0.02 μmol(CO2) m –2 s –1 ], associated to the lowest PN rates (44 % of the maximum) and carbon use efficiency (CUE) in July underlined the mobilization of stored material during drought stress by a higher air temperature (32.7 °C).
Keywords: carbon use efficiency; Leaf temperature; seasonal course